Bezrobocie en face, czyli psychologiczne aspekty bezrobocia - Ciuk, Sylwia (Kultura i Społeczeństwo, 2008)
The purpose of this paper is to present the problem of unemployment from a new and fairly untypical perspective which was achieved thanks to the adopted form of narrative. The text consists of two stories about the experience of being unemployed: one told by the jobless person and the other by his life partner who is also the author of this article. The two stories later merge in the ﬁnal section of the article where the fragments of the life-world of the unemployed and his partner presented here are juxtaposed with a wider discourse and reﬂection upon unemployment.